Kaisa: Jurnal Pendidikan dan Pembelajaran: Hakikat Kurikullum dalam Perspektif Filsafat Pendidikan Islam - Supriyanto, Adi; Fitriani, Aida; Sofiani, Azrina; Izzati, Nurfatin; Syafika, Tria Nur; Mukhlas (STAIN Bengkalis, 2024)
Philosophy plays an important role in directing the goals of general education and ensuring the curriculum reflects Islamic values that are in line with universal truths. This journal discusses the Islamic. Education curriculum and curriculum from the perspective of Islamic education philosophy. This journal was created to show that through a philosophical approach it can be decided how to measure success in the educational process by referring to curriculum principles involving philosophical, psychological, social, and organization. This Islamic education curriculum also has unique characteristic, where the structure of Islamic education is based on principles and learning materials sourced from the Al-Qur’an and the hadith of the prophet. Filsafat memegang peran penting dalam mengarahkan tujuan pendidikan umum dan memastikan kurikulum mencerminkan nilai-nilai Islam yang sejalan dengan kebenaran universal. Dalam jurnal ini membahas Kurikulum pendidikan Islam dan kurikulum dalam perspektif filsafat pendidikan Islam. Jurnal ini dibuat untuk menunjukkan bahwa melalui pendekatan filsafat dapat diputuskan bagaimana mengukur sebuah kesuksesan dalam proses pendidikan dengan merujuk pada asas-asas kurikulum yang melibatkan asas filosofis, psikologis, sosiologis, dan organisasi. Kurikulum pendidikan Islam ini juga memiliki ciri khas, dimana struktur pendidikan Islam didasarkan pada prinsip-prinsip dan materi pembelajaran yang bersumber dari Al-Qur’an dan Hadits Nabi.